Becoming Home: Revisiting Arne Naess toward an Ecophilosophy and a Depth Ecology for the 22nd Century - Haukeland, Per Ingvar (The Trumpeter, 2023)
This article is set in the context of a worsening ecological crisis, which is interpreted as an existential life crisis. The ecocrisis is not just about nature, but also a crisis of culture, community, and self. The prefix “eco” is interpreted in as “home in life”. To solve the crisis, we need a balanced focus on ecophilia and ecojustice. It is not enough to care, to solve the crisis we need to address issues of justice. Naess said he was optimistic on behalf of the 22nd century, but how bad it gets before it gets better depends on what we do today. In the article, I will revisit the life and works of Naess to explore what may inspire a sustainable and eco-friendly future. It will show there is a need to put “philo” back into ecosophy and to go deeper into the depths of deep ecology in a depth ecology movement. It will also address some issues, such as that of eco-animism and a renewed sense of the sacred.